Medullary aplasia associated with Human T-Cell Lymphotropic Virus Type 1 (HTLV-1): A Case Report - Ccorahua-Rios, Maycol Suker (2021)
Background: Medullary aplasia is a disease characterized by pancytopenia with hypocellular bone marrow. Most of these are acquired and can be idiopathic or secondary to bone marrow damage produced by physical, chemical or infectious agents. HTLV-1 is an intracellular retrovirus that is transmitted by prolonged breastfeeding, sexual intercourse, and blood transfusions. Case description: We report the case of a 28-year-old woman who presented petechiae, gingivorrhagia, and generalized paleness. In the laboratory examination, severe pancytopenia was found, HTLV-1 positive, and in the bone marrow aspirate, marked hypocellularity. She received antibiotics, antifungals, antivirals, and immunosuppressive agents with a steady course. Conclusions: HTLV-1 infection is common in Peru; however, its association with medullary aplasia is poorly described. Hematopoietic stem-cell transplantation is an alternative treatment in case of failure to respond to immunosuppressive therapy.